Automatic greenhouse watering system using microcontroller - Hussein, Masayu (2007)
Greenhouse is often used for growing flowers, vegetables, fruits, and tobacco plants. The closed environment of a greenhouse has its own unique requirements, compared with outdoor production. Pests and diseases, and extremes of heat and humidity, have to be controlled, and irrigation is necessary to provide water. Because of these reasons, sensors are needed to automatically control the watering system in the greenhouse. In this project, it uses two sensors which are soil moisture detector and temperature sensor to control the watering system. The valve is used to control the outlet flow of the watering. Once the temperature sensor detect that the environment temperature is lower than the predetermined temperature value, the valve will be in the off state and vice versa. The soil moisture detector gives input to the microcontroller whether watering is needed or not depends on the moisture of the soil. If the soil is dry, the valve will be activated. The water level sensor is use only to monitor the water level. It is important to monitor the water level in case of drought.